Assessing suitability of the ACRU hydrological model in a rainforest catchment in Ghana, West Africa - Jewitt, G.P.W. (2020)
The objective of this study was to assess the suitability of the daily time step physical-conceptual ACRU model for hydrological modelling in the Bonsa catchment. Since the catchment is data poor, model calibration was conducted using a careful parameterization and sensitivity analysis, using initial values obtained from literature and field observations, as well as climate data for the period 1987–1999 and 1991 land use. The model performance during calibration and validation was satisfactory, with a monthly NSE of 0.6 and 0.5 and R2 of 0.8 and 0.7, respectively. The model simulated the rise and the recession of the hydrograph well, but during the validation the accumulated monthly streamflows were underestimated by 10%. The main conclusion from this study is that the ACRU hydrological model is suitable for exploring basic hydrological responses to land use and climate in the Bonsa and similar catchments.